A Woman with Tuberculosis Multidrug Resistance and QTc Prolongation Repetitive Interval: A Case Report - Tutik Kusmiati; Ni Made Mertaniasih; Johanes Nugroho Eko Putranto; Budi Suprapti; Soedarsono; Abdul Rahman Bahmid (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : Prolonged QTc interval is one of the side effects of the short-regimen MDR-TB. QTcprolongation is a risk factor for Torsades de pointes and is influenced by many factors. Case : 47-year-oldwoman who was diagnosed with MDR-TB through GeneXpert examination and received short-regimenMDR-TB. This patient experienced repeated QTc prolongation, with peak QTc interval 600 msec occurringat 4th month with mild hypokalemia without clinical symptoms. The patient completed 9 months of shortregimentherapy with improve chest x ray followed by negative sputum culture. Conclusion : Short-regimenMDR-TB contains several drugs that cause QTc prolongation. Clinical evaluation is required in patientswith QTc prolongation before changing the regiment.